The Effectiveness of Mobile Learning in the Form of Performance Support System in Higher Education - Mileva, Nevena (International Journal of Interactive Mobile Technologies (iJIM), 2011)
Students in engineering education need high-quality educational materials, and what is the most important, continually up-to-dated courses. The students need a possibility to self-assess their skills and knowledge as the learning steps for improvement - the courses, will provide them knowledge on the newest achievements in the field of engineering. The complexity of the knowledge and skills, necessary to perform successfully the tasks, determines the learnersâ?? needs of â??practical learning